Blind beauty - Peyton, K. M. (London : Scholastic Children's Books, 2014)
Teenage Tessa's passion for riding and her love for an ugly horse named Buffoon help her endure an unhappy life in the English countryside with a hateful stepfather.
"Originally published in Great Britain 1999 by Scholastic Ltd., London"--T.p. verso.
Young Adult.
Young Adult
Keywords: Horse racing -- Fiction; Horses -- Fiction; Stepfathers -- Fiction; Horse racing -- Fiction; Horses -- Fiction; Stepfathers -- Fiction; England -- Fiction; England -- Fiction